Novel Insights Into The Role Of Serum Interleukin-39 In Patients With Systemic Lupus Erythematosus - Al Rubaye , Amal Mahdi; Sharquie, Inas K.; Gorial, Faiq I. (Iraqi Journal of Science, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that has a genetic predisposition and a complex pathogenesis in which the involvement of various cytokines has been shown. In the current study, serum interleukin-39 (IL-39) levels from 99 patients with SLE and 33 healthy control subjects who attended the Baghdad Teaching Hospital Rheumatology Unit were examined. Patients were divided into 3 subgroups according to disease status: inactive (n = 33), active moderate (n = 33), and active severe (n = 33). This topic has not yet been explored, so the significance of IL-39 as a biomarker for SLE was evaluated. Cytokine levels were measured using enzyme-linked immunosorbent assay kits. Full medical histories, body mass index, gender, and clinical disease activity, the latter evaluated using the SLE disease activity index, were documented. Laboratory disease parameters, including anti-dsDNA antibodies, C3 and C4 levels, erythrocyte sedimentation rate, and C-reactive protein titres, were measured. The mean age of patients was 33.92 ± 0.91 years. The IL-39 level was higher in patients (13.70 ± 0.35 ng/l) than in controls (10.67 ± 0.19 ng/l, p < 0.01). The mean of IL-39 levels was highest in patients with active severe SLE (17.42 ± 0.48 ng/l) and then became incrementally lower with reducing disease severity, i.e., active moderate, 13.34 ± 0.23 ng/l; inactive, 10.93 ± 0.24 ng/l. Serum IL-39 showed good validity for the diagnosis of SLE. With a cut-off value ≥ 10.25 ng/l and an area under the curve of 0.79, diagnostic sensitivity, accuracy, and specificity were 79.98%, 51.5%, and 71.97%, respectively. In conclusion, serum IL-39 levels were significantly higher in patients with SLE than in healthy controls and were correlated with disease activity. This interleukin may be useful in predicting disease severity.